GALERI MATERIAL ARSITEKTUR NUSANTARA DI JAKARTA - Gusti Nur Rakhman Qowiyya Al Haq; Irwan Yudha Hadinata (ULM Press, 2024)
Nusantara Architectural Materials Gallery in Jakarta emerged from local materials and craftsmanship which began to be abandoned due to the proliferation of developments that prefer to use conventional materials. This raises the potential to develop a gallery design that focuses on preserving the Nusantara Architecture. The purpose of this design is to get a design by utilizing Local Material and Craft Commercialization, Education, and Innovation united in the concept of gotong-royong Flexspace. the application of this concept with a locality method approach in the forms design, activity-programs, atmosphere and building visuals. then it can create a forum for collaboration between craftsmen and the community to help preserve the Nusantara architecture.